Exacerbation of Allergic Diseases by Chemicals: Role of TSLP - Ryosuke Segawa; Noriyasu Hirasawa (Elsevier, 2014)
Environmental chemicals, such as cigarette smoke and diesel exhaust, have been reported as risk factors that exacerbate allergic diseases. However, the exacerbation mechanisms induced by these chemicals are not yet fully understood. Thymic stromal lymphopoietin (TSLP) is produced mainly by epithelial cells and plays an important role as a master switch of allergic inflammation because it promotes Th2-type immune responses by inducing the activation of dendritic cells. Chemical compounds, such as formalin, have been shown to bind to proteins and form a new antigen that induces allergic responses. A second group of chemicals that enhance allergic responses to exogenous proteins have also been reported. We recently demonstrated that some of these chemicals induced TSLP production and may potentially augment Th2-type allergic responses. We proposed that TSLP-producing chemical compounds should be recognized as chemical allegro-accelerators. Keywords:: thymic stromal lymphopoietin, environmental chemical, allergy